Evaluation of bond durability of different self-adhesive bioactive restorative systems to dentin - Fawkia M. Samy; Naglaa R. El-Kholany; Hamdi H. Hamama (Scientific Reports)
Abstract This study aimed to compare the bonding efficacy three bioactive self-adhesive restorative systems to dentin. A total of 80 permanent human molars were utilized in this study. The occlusal enamel was removed to exposed mid-coronal dentin; 40 molars were used for microshear bond strength testing, while the remaining molars were used for micromorphological analysis of restoration/dentin interface. Accordingly, 4 groups were assigned according to the used restorative materials; (G1) self-adhesive hybrid composite (surefil one), (G2) Alkasite-based material (Cention forte) without pretreatment primer, (G3) Alkasite-based material (Cention forte) with pretreatment primer (Cention primer), and (G4) resin-modified glass ionomer (fuji II LC). Then each group was divided into 2 sub-group according to testing time (n = 5); immediate (after 24 h) and delayed (after 6 months of storage in artificial saliva). Microshear bond strength testing employed a universal testing machine to quantify the force required for material fracture at the interface, followed by failure mode analysis. Interfacial micromorphology was assessed using scanning electron microscopy (SEM). In µSBS, the outcome of Two-way ANOVA showed that, there is a statistically significant difference in “type of the restorative material” and “storage time” (p˂0.05. The output of Tukey post-hoc test revealed highest µSBS values were recorded in both immediate and delayed was recorded for Cention Forte with it’s pretreatment primer (p < 0.05). Whereas Surefil one & Cention Forte (without primer) showed the lowest µSBS results among its immediate and delayed groups (p < 0.05). Regarding the micromorphological patterns of restoration/dentin interface using SEM, there was a difference among the tested groups. This study revealed that using of primers prior to application of alkasite-based restorative material is highly recommended as this techniques seems to be the most effective in obtaining superior bond strength with dentin. Accordingly, this outcome of this study highlighting the importance of using primer in enhancing bonding to dentin, which might slightly countered the initial manufacturer’s recommendations and categorization of this type of restorations as a self-adhesive.